2019
DOI: 10.9778/cmajo.20180202
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making experienced by Canadians facing health care decisions: a Web-based survey

Abstract: anadians need support in health-related decisionmaking.¹ More than half of Canadians experience decisional conflict after having made a complex health decision. 1 Many of the decisions patients face present multiple options, there is incomplete or conflicting evidence about possible outcomes, and expectations are often unrealistic. 1,2 Shared decision-making is a process whereby health care professionals and patients work jointly to make health care choices, considering best clinical evidence as well as patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 24 publications
2
55
2
Order By: Relevance
“…Moreover, the small group of studies that examined the perspectives of patients, caregivers, and clinicians regarding the use of these tools reported that they support their use. Yet, shared decision-making is underused in clinical practice [51][52][53], likely due to the time and resources required in order for it to be effective [54]. Embracing shared decision-making as a strategy for reducing low-value care will require appropriate infrastructure within the healthcare system and cultural shift among patients and clinicians; however, as highlighted in a recent commentary on the complexities of deimplementation [15], taking such measures to address patient-level factors that affect de-implementation will be the key to the success of future de-implementation initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the small group of studies that examined the perspectives of patients, caregivers, and clinicians regarding the use of these tools reported that they support their use. Yet, shared decision-making is underused in clinical practice [51][52][53], likely due to the time and resources required in order for it to be effective [54]. Embracing shared decision-making as a strategy for reducing low-value care will require appropriate infrastructure within the healthcare system and cultural shift among patients and clinicians; however, as highlighted in a recent commentary on the complexities of deimplementation [15], taking such measures to address patient-level factors that affect de-implementation will be the key to the success of future de-implementation initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians lack understanding of the decision‐making needs faced by primary care patients with complex care needs, which increases the imbalance between their needs and the services currently offered by interprofessional teams. This is an important issue to address because it is now known that Canadians experience a low degree of SDM, and that most patients do not have the opportunity to talk about their preferences in terms of care and treatment. Patients could greatly benefit from the SDM approach, but it is often unknown to health care professionals and requires to be well informed about the “real‐life” of living with a complex health condition .…”
Section: Discussionmentioning
confidence: 99%
“…Patients could greatly benefit from the SDM approach, 27,28 but it is often unknown to health care professionals and requires to be well informed about the "real-life" of living with a complex health condition. 23 The SDM approach is underutilized among vulnerable clienteles 3,29 ; health professionals presume that they wish to be less active in decision making about their health care. 30 The huge number of decisions faced by patients in our study supports that patients would benefit from a Patient Decision Aid (PtDA) to discuss engaging or not in a decision making case management program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations